INDICADORES DE SUSTENTABILIDADE PARA PROGRAMAS DE EFICIÊNCIA ENERGÉTICA E HÍDRICA NO SANEAMENTO AMBIENTAL. O CASO PROCEL SANEAR / ELETROBRAS. - Santos, Maria Cristina de Almeida (2008)
This dissertation presents a proposal for sustainability indicators to measure the effectiveness of hydric and energy efficiency programs in domestic urban environmental sanitation, according to principles of sustainable development. The sustainability indicators were developed following a theoretical approach and integrating the three dimensions of the sustainable development (The Triple Bottom Line): the social one, related to providing for basic needs, to improving living standards, and to social justice; the environmental one, associated to the rational use of natural resources and to the preservation and restoration of the environment; and the economic one, reflected in financial performance and standards of consumption of water and energy. The development of sustainability indicators is part of national and international efforts for the achievement of the aims set down in Agenda 21, regarding the elaboration of tools for project follow-ups and for decision-making support aimed at achieving sustainable development. The dissertation end product is a set of indicators, verified by energy efficiency specialists with substantial expertise in the sanitation field. The set of indicators was built from the case study PROCEL SANEAR, a governamental programme managed by Centrais Elétricas Brasileiras S.A. (ELETROBRAS).